Measurement and structural modelling on factors of islamic payment gateway system among millennial generation in Malaysia - Bakri, Mohammed Hariri; Mat Rasid, Ahmad Mujahid; De Mello, Geraldine John Philip; Ismail, Albert Feisal @ Muhd Feisal; Md Razak, Mohamad Idham (People and Global Business Association, 2023)
Purpose: This study aims to develop a conceptual model and validate the model using a unified theory of acceptance and use of technology to determine the Determinants of Intention to Use the Islamic Payment Gateway System among the Millennial Generation in Malaysia via a Structural Model. Based on past research, the UTAUT hypothe-sises four variable constructs: performance expectancy, effort expectancy, social Influence, and facilitating factors. These characteristics are predictive of behavioural intent. In terms of the study, the author added a religiosity variable instead of the four recommended moderators. Design/methodology/approach: A total of 303 field tests have been obtained from Malaysian millennial citizens using Islamic Fintech. Before the data is analysed into exploratory factor analysis, preliminary analysis such as normality and multicollinearity test has been conducted. Findings: All constructs, which are performance expectancy, effort expectancy, social Influence, facilitating condition, and behavioural intention with religiosity as the moderating, have no factor reduction, but all constructs identified two components under exploratory factor analysis. Moreover, all construct KMO tests more than 0.50. All constructs met unidimensionality, validity, reliability, and model fitness in CFA. All the requirements for model fit in this study have been achieved. Research limitations/implications: This study has significant consequences, particularly for the existing payment gateway system, which is already entering every area of human lifestyle with the millennial generation being targeted as the native user. Originality/value: This study fills the apparent gap in the existing payment gateway system literature by assessing religiosity as moderating through exploratory factor analysis.